Optogenetics for Retinal Disorders - Bradley S Henriksen; Robert E Marc; Paul S Bernstein (Journal of Ophthalmic & Vision Research, 2014)
Optogenetics is the use of genetic methods combined with optical technology to achieve gain or loss of function within neuronal circuits. The field of optogenetics has been rapidly expanding in efforts to restore visual function to blinding diseases such as retinitis pigmentosa (RP). Most work in the field includes a group of light-sensitive retinaldehyde-binding proteins known as opsins. Opsins couple photon absorption to molecular signaling chains that control cellular ion currents. Targeting of opsin genes to surviving retinal cells is fundamental to the success of optogenetic therapy. Viral delivery, primarily adeno-associated virus, using intravitreal injection for inner retinal cells and subretinal injection for outer retinal cells, has proven successful in many models. Challenges in bioengineering remain for optogenetics including relative insensitivity of opsins to physiologic light levels of stimulation and difficulty with viral delivery in primate models. However, targeting optogenetic therapy may present an even greater challenge. Neural and glial remodeling seen in advanced stages of RP result in reorganization of remaining neural retina, and optogenetic therapy may not yield functional results. Remodeling also poses a challenge to the selection of cellular targets, with bipolar, amacrine and ganglion cells all playing distinct physiologic roles, and affected by remodeling differently. Although optogenetics has drawn closer to clinical utility, advances in opsin engineering, therapeutic targeting and ultimately in molecular inhibition of remodeling will play critical roles in the continued clinical advancement of optogenetic therapy.